Bibliometric analysis of Financial Risk Management - Ahmad, Iftikhar; Iqbal, Shahid; Naz, Farah; Jamil, Shahzad; Haider, Ijlal (The journal of contemporary issues in business and government, 2021)
Financial risk management enhances financialperformance and effectiveness, and it has been recently received research recognition and momentum.This study aims to adopt a bibliometric analysis of financial risk management to identify the research trends and opportunities related to diverse types of research papers published in journals and conferences indexed by Web of Science for the years 2004-2018. The main objectives of this study include finding the research trend of financial risk management publications and citations, top research areas, the most influential papers based on citation count, the top supportive funding agencies, and the future research direction. This bibliometric study indicates that the interest of researchers is increasing in financial risk management every year due to an unpredictable environment and economic situation. The number of citations to financial risk management research papers has been growing. The top research areas in financial risk management include business economics, environmental sciences ecology, engineering, mathematics, and operation research management science. The analysis indicates that the National Natural Science Foundation of China supports most of the financial risk management research by funding the research. This reflects the vast interests and trends of financial risk management among researchers. This study can be a valuable learning point for young researchers to find attractive, relevant research insights withinfinancial risk management.